A quick guide to Filipino food and cooking - Abiva, Cris C. (Manila, Philippines : Anvil Publications, 2001)
Over the years, many books have been written about Filipino cooking and eating traditions. There have also been cookbooks on local and regional cuisine. This book aims to help students who will take up food courses or in courses involving food and its preparation or preservation .
Keywords: FILIPINO COOKING -- GUIDEBOOK